A survey overview: on wireless body area network and its various applications - Vandana. T, Santhi; Ravi. K, Sreenivasa (International Journal of Engineering and Technology, 2018)
With the remarkable change of mobile radio communication over the past years in the wireless communication technologies, makes the Wireless Body Area Network (WBAN) services to be adopted by most of the people around the world. Wireless body area network is such a special purpose sensor network that was made for continues monitoring the health parameters in real time with the different wire-less sensors by implanting internally or externally of a human body. This wireless sensed information from the vital organs of the human body may be in the form of data, voice, video signals are communicated wirelessly through WBAN. This survey article presents an overview on- the WBAN communication architecture, comparison of WBAN and Wireless Sensor Networks (WSN), WBAN operating protocols- those are intended for short range wireless communication, and its applications in the medical and non- medical field have been out lined.Â Â